Czym jest dziś czytanie literatury? (ankieta) - Jarniewicz, Jerzy (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
In response to the questionnaire, Professor Jerzy Jarniewicz explains why it is impossible and pointless to choose the best or the most important book, discusses his fascination with Justyna Bargielska’s writings, and talks about returning time and time again to (seemingly?) well-known works.